"All too human" or the emergence of a techno-induced feeling of being less-able: identity work, ableism and new service technologies. Issue 22 (16th December 2022) - Moulaï, Kamila; Islam, Gazi; Manning, Stephan; Terlinden, Laurianne
Abstract: The increasing use of semi-automated technologies in service work has implications for employee's conceptions of their own abilities, and their processes of identification at work. Drawing on theorizing from the identity literature, we examine how employees come to think about their own abilities in relation to and in comparison to machinic norms, creating unattainable expectations of an "ideal worker". Through a qualitative case study of the introduction of a semi-automated system in a supermarket service setting, we examine cashiers' sense of devaluation on the basis of their humanness, which comes to be seen as of a less-abled nature in relation to the automated system. We show how cashier perceptions of customers' changing interaction norms contribute to this sense of identity void, as traditional encounters of care or mutual regard are replaced by automated processes. We discuss the implications for Human Resource Management, laying out a future research agenda around identity processes and human-technology interaction.